UNDERPRICING PERUSAHAAN NON KEUANGAN PADA MASA COVID-19: FAKTOR YANG MEMPENGARUHI - Umi Murtini; Hizkia Winandra Dwi Kurnia (Fakultas Bisnis Universitas Kristen Duta Wacana, 2024)
ABSTRACT This research aims to examine the influence of capital structure, effective use of assets, reputation of the underwriter, size of the board of directors and number of independent commissioners in non-financial companies conducting an IPO on the Indonesia Stock Exchange during the Covid-19 period on the amount of underpricing. Underpricing is measured using the percentage change in price during the IPO with the closing price of shares on the first day of transactions on the Indonesian Stock Exchange. The sampling method used was purposive sampling and 63 companies were obtained as research samples. Hypothesis testing used weighted least squares (WLS). The research results conclude that capital structure and independent commissioners have no effect on underpricing. The effectiveness of asset use and the underwriter's reputation have a positive effect and the size of the board of commissioners has a negative effect on underpricing. Keywords: underpricing, covid-19, capital structure, board and commissioner size, effective use of assets. ABSTRAK Penelitian ini bertujuan menguji pengaruh struktur modal, efektifitas penggunaan asset, reputasi penjamin emisi, ukuran dewan direksi dan jumlah komisaris independen di perusahaan non keuangan yang melakukan IPO di Bursa Efek Indonesia pada masa covid-19 pada besarnya underpricing. Underpricing diukur menggunakan persentase perubahan harga saat IPO dengan harga penutupan saham di hari pertama ditransaksikan di Bursa Efek Indonesia. Metoda sampling digunakan purposive sampling dan diperoleh 63 perusahaan sebagai sampel penelitian. Uji hipotesis digunakan weigted least square (WLS). Hasil penelitian menyimpulkan bahwa struktur modal dan komisaris independent tidak berpengaruh terhadap underpricing. Efektifitas penggunaan asset dan reputasi penjamin emisi berpengaruh positif dan ukuran komisaris berpengaruh negative terhadap underpricing. Kata Kunci: underpricing, covid-19, struktur modal, ukuran dewan dan komisaris, Efektifitas penggunaan aset